Partial Purified, Characterization and Antibacterial Activity of Bacteriocin from Leuconostoc Mesenteroides: Life Sciences-Microbiology for better Health Care - Enas Nabil Danial; Salha Hassan Mastour Al-Zahrani; Zahra Al-Hassan Mohammad Al-Mahmoudi (International Journal of Life Science and Pharma Research, 2022)
Lactic acid bacteria produces a variety of antibacterial compounds such as organic acids, diacetyl, hydrogen peroxide and bacteriocins or bactericidal proteins as byproducts of fermentation. Bacteriocins are small proteins with bactericidal or bacteriostatic activity against genetically closely related species. Some bacteriocins are peptides consisting of only 13 to 37 amino acids. Some small bacteriocins contain unusual amino acids originating from modifications of conventional amino acids after translation. Bacteriocins are natural peptides secreted by several bacteria that exert bactericidal activity against other bacterial species. Research in this topic is promoted not only by the need to develop alternatives to antibiotics and drugs that have shown non-desirable effects, but also to the capacity of some bacteriocins to inhibit saprophytic and food-borne pathogens in food stuffs. The purification of bacteriocins produced is helpful for the knowledge of the mechanism of action, structure, and other characteristics, which helps to isolate the bacteriocin biosynthetic genes. In this study, purified bacteriocins from Leuconostoc mesenteroides were described. The frequently applied techniques involve ammonium sulfate salt precipitation. The results obtained through the purification of Leuconostoc mesentroides bacteriocins carried out its antimicrobial activity, thermostable and the effected of pH. the incubation of temperature on bacteriocin activity in terms of inhibition zones. The data recorded that the bacteriocin was active in a wide range of pH, the maximum activity was observed at pH 6.0 to 7.0, but at high pH of 8.0 the activity of the bacteriocin gradually decreased. Bacteriocin could retain its antimicrobial activity partially when there was a shift to acidic or basic range. It has been found to be thermo stable in nature as it can withstand high temperatures up to 121°C, although a partial loss in the activity was observed with a continuous increase in temperature. Bacteriocins carried out for its antimicrobial activity, thermostable and the effect of pH.